1. The Synthesis And Biologi Calactivity of Some Estragole Analogues Towards Oil Palm Pollinating Weevils Elaeidobius Kamerunicus Faust 2. Alkaloid Constituents of Breynia Coronata (Euphorbiaceae) - Abu Hassan, Hazimah (1990)
Estragole is an attractant for the weevils Elaeidobi us kamerunicus Faust. The weevils were recently identified as an efficient pollinator of the oil palm, Elaeis guineens is Jacq. Four organic compounds,analogous to estrago1e, namely: 4-ethoxyallylbenzene, 4-isopropoxyallylenzene, 3-(4-methoxy phenyl)methyloxirane and (4-methoxyphenyl)acetaldehyde were prepared in the laboratory. Bioassay using a Y-tube olfactometer was carried out for each analogue in order to test its activity as an attractant for the weevils kamerunicus. Attractancy tests against water indicated that none of the analogues were active except for 4-ethoxyallyl benzene.